Socialization and Assistance in the Registration of the Legality of the P-IRT Business for Local MSME Leading Products in Ciburial Village, Bandung Regency - Yunita Mafruhat, Ade; Haryatiningsih, Ria; Haviza, Meidy; Alya Prameswari, Khofifah; Dwifany Lesmana, Lovie; Farihatunisa, Ranti; Nuha Rabbani, Adiba; ., Resti; Aryani Ramlib, Tatty; Fauzi Arif, Muhammad; et al. (KnE Social Sciences, 2023)
This article aims to show that there is an increase in the knowledge and awareness of MSMEs in legalizing leading micro, small, and medium enterprises (MSMEs) Ciburial Village through community service activities (CSA) through socialization and assistance in Ciburial Village. Based on the initial survey conducted by the team in Ciburial Village, information was obtained that quite a lot of SMEs in Ciburial Village have the potential to have high competitiveness. However, one of the problems faced by MSMEs is the lack of interest and awareness of the actors in registering their businesses legally. The implementation methods used include field surveys, socialization, mentoring, questionnaire distribution, different tests, documentation, and preparation of the final report. The results of the PKM activity show that there are differences in knowledge and awareness before and after the activity. This difference is indicated by the different test results where Sig. (2-Mean Std. tailed) <0.05. Meanwhile, the increase in awareness is shown by the increase in the registration of home industry food license (P-IRT) MSMEs in Ciburial Village. Keywords: MSMEs, business legality, business management